Peritoneal Nebulization of Ropivacaine during Laparoscopic Cholecystectomy: Dose Finding and Pharmacokinetic Study. (20th February 2017) - Allegri, Massimo; Ornaghi, Martina; Ferland, Catherine E.; Bugada, Dario; Meghani, Yash; Calcinati, Serena; De Gregori, Manuela; Lovisari, Federica; Radhakrishnan, Krishnaprabha; Cusato, Maria; Scalia Catenacci, Stefano; Somaini, Marta; et al.
Abstract : Background . Intraperitoneal nebulization of ropivacaine reduces postoperative pain and morphine consumption after laparoscopic surgery. The aim of this multicenter double-blind randomized controlled trial was to assess the efficacy of different doses and dose-related absorption of ropivacaine when nebulized in the peritoneal cavity during laparoscopic cholecystectomy. Methods . Patients were randomized to receive 50, 100, or 150 mg of ropivacaine 1% by peritoneal nebulization through a nebulizer. Morphine consumption, pain intensity in the abdomen, wound and shoulder, time to unassisted ambulation, discharge time, and adverse effects were collected during the first 48 hours after surgery. The pharmacokinetics of ropivacaine was evaluated using high performance liquid chromatography. Results . Nebulization of 50 mg of ropivacaine had the same effect of 100 or 150 mg in terms of postoperative morphine consumption, shoulder pain, postoperative nausea and vomiting, activity resumption, and hospital discharge timing (>0.05). Plasma concentrations did not reach toxic levels in any patient, and no significant differences were observed between groups (P > 0.05 ). Conclusions . There is no enhancement in analgesic efficacy with higher doses of nebulized ropivacaine during laparoscopic cholecystectomy. When administered with a microvibration-based aerosol humidification system, the pharmacokinetics of ropivacaine is constant and maintains an adequate safety profile for each dosage tested.